Detection of caprine paratuberculosis (Johne's disease) in pre- and post-vaccinated herds: morphological diagnosis, lesion grading, and bacterial identification - Stefanova, Elena Plamenova; Sierra, Eva; Fernández, Antonio; Quesada-Canales, Oscar; Paz-Sánchez, Yania; Colom-Rivero, Ana; Espinosa de los Monteros, Antonio; Herráez, Pedro; Domínguez, Lucas; Bezos, Javier; Pérez-Sancho, Marta; Moreno, Inmaculada; et al. (Frontiers in Veterinary Science, 2024)
Samples from mesenteric lymph nodes (MS LNs) and ileocecal valve (ICV) of 105 goats (61 non-vaccinated and 44 vaccinated anti-Mycobacterium avium subspecies paratuberculosis (MAP)) with subclinical infection from a farm with confirmed history of paratuberculosis (PTB) were collected at slaughter. PTB-compatible lesions were graded separately in MS LNs and in ICV lamina propria (LP) and Peyer´s patches (PPs). Furthermore, the load of acid-fast bacilli was quantified by Ziehl-Neelsen (ZN), MAP antigens by immunohistochemistry (IHC) and MAP DNA by PCR targeting the IS900 sequence. Gross PTB-compatible lesions were detected in 39% of the goats, 31.72% were vaccinated (V) and 68.29% were non-vaccinated (nV). Histopathological MAP-induced lesions were identified in 58% of the animals, 36.07% were V and 63.93% were nV. By adding histopathology as a diagnostic tool, the increase in the diagnosed cases was of 28% in MS LNs and 86.05% in ICV. Grade IV granulomas with central mineralization and necrosis were the most common lesion in MS LNs. Mild granulomatous enteritis with multifocal foci of epithelioid macrophages predominated in the ICV, being more frequent in the PPs than in the LP. Furthermore, statistical differences were demonstrated between the vaccinated and non-vaccinated animals regarding the presence of histopathological lesions in MS LNs, ICV LP and ICV PPs. More non-vaccinated animals tested positive by ZN, IHC and PCR which demonstrates benefit of anti-MAP vaccination on the reduction of PTB lesions and bacterial load in target organs. Our results highlight the importance of the combination of gross and histopathological assessment with different laboratory techniques for correct PTB morphological and etiological diagnosis in both vaccinated and non-vaccinated naturally infected goats with subclinical disease. Nevertheless, further studies are needed to optimize sampling protocols in goat subclinical PTB in order to improve the agreement between the diagnostic tools.